Efeitos da suplementação com Glutamina e Glutamato em cães com enterite hemorrágica - RODRIGUES, Armele Karina da Silva (2016)
We know that glutamine performs many functions in the body as well as being an important energy source for the enterocytes and immune system, the intention was to evaluate the effect of supplementation with Glutamine (GLN) and Glutamate (GLU) on hematologic variables and biochemical in dogs that presented clinical enteritis. 15 dogs were selected and divided into two groups: Group 01 (G-CON) - 5 animals and Group 02 (G-GLN) - 10 animals. The animals of the group 01 were subjected to medical treatment without supplementation and animals belonging to the group 02 were submitted to clinical treatment and supplemented with GLN and GLU (Aminogut®, Ajinomoto of Brazil) orally for a period of 14 days. It was conducted blood count of these animals and determination of GLN, GLU, total protein (TP), albumin (ALB), globulin (GLOB), urea (UR), creatinine (CREAT), aspartate aminotransferase (AST), alanine aminotransferase (ALT), total cholesterol and triglycerides. The results obtained were submitted to ANOVA and Tukey test, it was established the level of significance of 5%. After analyzing the results It has been observed alterations in the concentrations of GLN and GLU, PPT, GLOB, ALB, UR and triglycerides (P <0.05). The count of erythrocytes, hemoglobin concentration, percentage of hematocrit, RBC indices and platelets count did not differ (P> 0.05). The leucocyte count showed significant change in the total white blood cell values, neutrophils and lymphocytes (P <0.05), the other parameters analyzed did not show statistical change (P> 0.05). We concluded that canines with enteritis, supplementation with a mixture of GLN + GLU associated with drug treatment was capable of producing elevation in immune cells (leukocytes and lymphocytes), proteins and its fractions.